The equal division puzzle - empirical evidence on intergenerational transfers in Sweden - Henry Ohlsson (Uppsala University, Department of Economics, 2007)
The objective of this paper is to study to what extent parents divide their estates unequally between their children. Unequal sharing of parental transfers is, for example, a necessary condition for theories of altruistic (dynastic) behavior to hold. I use a new data set based on the estate reports for 230 widows, widowers, and divorcees from the city of Stockholm, Sweden deceased in 2004. Unequal sharing is unusual, depending on definitions only 725 percent of the estates are unequally divided. The data set is also used to estimate probit models for the likelihood of unequal sharing. A first main result is that the probability of unequal sharing is increasing in the size of the estate. Second, the older the children are on average the more likely is unequal sharing. Finally, unequal sharing is more common among deceased from some neighborhoods of the city compared to deceased from other neighborhoods.
urn:nbn:se:uu:diva-25385
Keywords: C81; D10; D31; D91; H24; 330; bequests; inheritances; equal division; altruism; Generationengerechtigkeit; Erbe; Verteilungsgerechtigkeit; Altruismus; Schweden